The Analysis of the Concept of “Kufr” (Arabic: کُفر, Denial or Rejection of Islam) in Fiqh (Arabic: فقه, Jurisprudence) and Kalām (Arabic: کلام, Philosophical Study of Islamic Theology) and Its Jurisprudential Consequences - Muhammad Ibrahim roushanzamir; mostafa mahdavi arjmand (آموزه‌‌های فقه مدني)
The widespread use of the word “Kufr” (Arabic: کفر, Denial or Rejection of Islam) in religious texts, having a wide range of religious and jurisprudential dimensions, and the topics related to it as one of the most important challenges of Islamic societies in the present era, requires careful examination of the meaning of this term and its components. This article, which is organized in descriptive-analytic manner, seeks to analyze the definition of this term and its features in the expression of jurists and theologians and examine their validity narrative documentation. The jurists and theologians have considered things such as: denial and falsification, ignorance, doubt about the existence of God and the Prophet’s prophecy, lack of faith, disrupting foundations such as oneness (Arabic: توحید, Romanized: Tawḥīd, assertion of the unity of God) and ʿAdal (Arabic: عدل, justice), and belief in the causes for leaving Islam as components of Kufr. The findings of this research indicate that among the mentioned features, only rejection and denial have strong validity narrative documentation, but other components are either not documented or have no strong documentation. Therefore, active Kufr is (denial and falsification) against beliefs, not just non-reaction.